2019
DOI: 10.1088/1757-899x/578/1/012072
|View full text |Cite
|
Sign up to set email alerts
|

One-pot solvothermal synthesis and characterization of UiO-66/HKUST-1 composites

Abstract: Metal-organic frameworks (MOFs) are promising crystalline materials for various application due to their controllable porous structure and large specific surface area. Their properties can be further improved by several means, such as making a binary MOF comprising of two different MOFs. In this research, UiO-66/HKUST-1 composites have been synthesized by solvothermal method, in which the UiO-66 was prepared at 120 °C for 24 h in N, N-dimethylformamide (DMF) prior to preparation of HKUST-1 at 100 °C for 10 h i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…One type of MOF that has a biocompatible property with fungus is Universitetet i Oslo-66 (UiO-66), which has advantages such as high thermal stability (up to 540 °C), large surface area, high porosity, and resilience in aqueous media. 21 Subsequently, this study continues a previous study using a different dye (RB5) on the same material. A previous study found that the beads could remove 88.29% of the methylene blue (MB) dye after 72 h. This study investigated RB5 dye degradation, including the kinetic, isotherm, and thermodynamic adsorption aspects and the influence of dye concentration, pH, and temperature parameters.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…One type of MOF that has a biocompatible property with fungus is Universitetet i Oslo-66 (UiO-66), which has advantages such as high thermal stability (up to 540 °C), large surface area, high porosity, and resilience in aqueous media. 21 Subsequently, this study continues a previous study using a different dye (RB5) on the same material. A previous study found that the beads could remove 88.29% of the methylene blue (MB) dye after 72 h. This study investigated RB5 dye degradation, including the kinetic, isotherm, and thermodynamic adsorption aspects and the influence of dye concentration, pH, and temperature parameters.…”
Section: Introductionmentioning
confidence: 67%
“…The synthesis of UiO-66 was carried out using the method from Ediati et al 21 with some modifications. Initially, two precursor solutions were made by adding 1.75 g of ZrCl 4 and 12.5 g of H 2 BDC each to two different Pyrex bottles containing 75 mL of DMF solvent, stirred with a magnetic stirrer for 15 min.…”
Section: Methodsmentioning
confidence: 99%